2006
DOI: 10.1063/1.2213931
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and optical properties of epitaxial rare-earth scandate films and their crystallization behavior

Abstract: Rare-earth scandates (ReScO3, with Re=Y, La, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, i.e., the entire series for which the individual oxides are chemically stable in contact with Si) were deposited in a temperature-gradient pulsed laser deposition system onto LaAlO3 substrates. The crystallization temperature depends monotonically on the Re atomic number and the Goldschmidt tolerance factor, with crystallization temperatures as low as 650°C for LaScO3 and PrScO3. The dielectric constants of the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 21 publications
2
54
1
Order By: Relevance
“…The GIXRD data of a 10 nm thick (Dy 0.5 Sc 0.5 ) 2 O 3 film in Figure 4 shows only a very weak peak around 31°, which most likely corresponds to a superposition of the (020) (112), and (200) reflections of orthorhombic perovskite DyScO 3 . [27] This large peak width (full width at half maximum (FWHM) of 3.5°) together with the low intensity of the GIXRD peak indicates that the as-grown (Dy 0.5 Sc 0.5 ) 2 O 3 layers are essentially amorphous. Annealing of the layer up to 1000°C does not change the GIXRD spectrum significantly, which indicates that the recrystallization temperature of (Dy 0.5 Sc 0.5 ) 2 O 3 is higher than 1000°C, [10] although this topic needs further consideration.…”
Section: Resultsmentioning
confidence: 98%
“…The GIXRD data of a 10 nm thick (Dy 0.5 Sc 0.5 ) 2 O 3 film in Figure 4 shows only a very weak peak around 31°, which most likely corresponds to a superposition of the (020) (112), and (200) reflections of orthorhombic perovskite DyScO 3 . [27] This large peak width (full width at half maximum (FWHM) of 3.5°) together with the low intensity of the GIXRD peak indicates that the as-grown (Dy 0.5 Sc 0.5 ) 2 O 3 layers are essentially amorphous. Annealing of the layer up to 1000°C does not change the GIXRD spectrum significantly, which indicates that the recrystallization temperature of (Dy 0.5 Sc 0.5 ) 2 O 3 is higher than 1000°C, [10] although this topic needs further consideration.…”
Section: Resultsmentioning
confidence: 98%
“…The importance of rare earth scandate crystals ReScO 3 (Re=La, Ce, Pr, Nd, Sm, Eu, Gd, Tb and Dy) used as substrates for epitaxial growth of perovskite thin films is based on excellent physical and chemical properties [1][2][3]. Figure 1 shows a DyScO 3 bulk crystal (cylinder diameter of about 32 mm) grown using the Czochralski (Cz) method.…”
Section: Introductionmentioning
confidence: 99%
“…12 Christen et al observed band gaps higher than 5.5 eV for these REScO 3 oxides and varying crystallization temperatures depending on the RE atomic number and the Goldschmidt tolerance factor. 12 According to their results, the crystallization temperature of SmScO 3 ͑750°C͒ lies intermediate between those of LaScO 3 ͑650°C͒ and GdScO 3 ͑800°C͒, however, among them it has the highest when crystallized. So far there are no experimental results about the application of amorphous SmScO 3 as a gate dielectric.…”
mentioning
confidence: 96%
“…7,8 In contrast, rare earth ͑RE͒ scandates ͑REScO 3 , RE=Gd, Dy, La͒ show higher and, therefore, have attracted significant attention for high-applications. [9][10][11][12][13] The amorphous RE scandates have between 20 and 30 and the crystalline phases have over 30. 12 Christen et al observed band gaps higher than 5.5 eV for these REScO 3 oxides and varying crystallization temperatures depending on the RE atomic number and the Goldschmidt tolerance factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation